Genograma e ecomapa como estratégias lúdicas de ensino de enfermagem na Atenção Primária à Saúde - Nayara Gonçalves Barbosa; Ana Carolina Guidorizzi Zanetti; Jacqueline de Souza
ABSTRACT Objectives: to report the experience using ludic strategies for the teaching-learning in the elaboration of the genogram and ecomap; and the use of these instruments by Nursing students in the Primary Health Care services. Methods: an experience report of the discipline Integrity of Care I (Integralidade do Cuidado I), of the Nursing School of Ribeirao Preto. Problems scenarios were created to approach the genogram and ecomap, comprising different family arrangements, represented by pedagogic puppets. Results: students actively participated, held collective discussions, elaborated genogram, and ecomap, identified the type of family, and the stages of the vital cycle, providing increased dynamics and interactivity. Subsequently, in supervised activities in Primary Health Care services, students elaborated the genogram and ecomap to monitor a family. Final Considerations: the use of ludic strategies propitiates the teamwork, active interaction of the group, and the creativity. The articulation between theory and practice resulted in a significant learning.